2019 ICA Early Career Award - Stinson, Michael (Canadian Acoustics, 2019)
The International Commission for Acoustics presented its Early Career Award to Professor Jérémie Voix, the President of the Canadian Acoustical Association (CAA). This short report describes the process and collects the memories from that important moment for our association.